ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KEBUMEN TAHUN 2013-2015 - Mispiyanti, Mispiyanti (P4M STIE Putra Bangsa, 2016)
Kebumen Regency is an autonomous region. The purpose is to improve the welfare of otonomi daerah and service to the community, the development of democracy, justice, and equity as well as the maintenance of harmonious relations between central and regional and inter-regional. Kebumen still dependent on grants from the central and provincial levels for Kebumen still can not be independent. However Kebumen still increase Pendapatan Asli Daerah (PAD). The object of this study was to Dinas Pendapatan Pengelolaan Keuangan and Aset Daerah (DPPKAD) Kebumen. The purpose of this study was to determine the contribution of Pajak Daerah and Retribusi Daerah on Pendapatan Asli Daerah (PAD). The data used in this research is quantitative data in the form of Pajak Daerah, Retribusi Daerah, Pendapatan Asli Daerah Year 2013-2015. The analysis used in this study is an analysis of revenue contribution of Pajak Daerah and Retribusi Daerah of the original income. The results showed the contribution of the Regional Pajak Daerah to Pendapatan Asli Daerah (PAD) in the year 2013 by 32%, in 2014 by 23%, in 2015 by 21%. Results Retribusi Daerah on Pendapatan Asli Daerah (PAD) in the year 2013 by 19%, in 2014 by 21%, in 2015 by 11%. In accordance with the criteria of the Pajak Daerah and Retribusi Daerah regions in Kebumen years 2013-2015 including the criteria have contributed greatly. Keywords: Otonomi Daerah, Pemerintah Daerah, Pendapatan Asli Daerah, Pajak Daerah, Retribusi Daerah, Kontribusi.